The Holy Name art of the Gesù : Bernini and his age - Wolk-Simon, Linda 1958-; Johns, Christopher M. S. 1955-; Bailey, Gauvin Alexander 1966-; Horn, Andrew; Levy, Evonne Anita 1961-; Mormando, Franco; O'Malley, John W. 1927-2022; Rice, Louise; Rosasco, Betsy; Salomon, Xavier F. 1979-; Scott, John B. 1946- (Saint Joseph's University Press, 2018)
This landmark exhibition, organized to commemorate Fairfield University's 75th anniversary, features artistic treasures from the Roman church of the Gesù never before seen in America: Bernini's bust of Roberto Bellarmino (patron saint of Fairfield University), Gaulli's monumental painted wood model of the apse, a gilt bronze altar sculpture by the versatile painter, draftsman and sculptor Ciro Ferri, the sumptuous jeweled cartegloria from the altar of St. Ignatius, and the magnificent embroidered chasuble of the church's great benefactor, Cardinal Alessandro Farnese. These masterpieces are joined by more than fifty paintings, sculptures, rare books, precious objects, drawings, prints, and historical documents by Bernini, Domenichino, Gaulli, Ciro Ferri, Carlo Maratti, and Andrea Pozzo, among other Italian Baroque masters, on loan from American museums and private collections. Exhibition: The Fairfield University Art Museum, USA (02.02.-19.05.2018)
Exhibition catalogue. - Ausstellungsdaten ermittelt
Keywords: Jesuiten; Geschichte 1600-1700; Kirchenbau; Ausstattung; Christliche Kunst; Kunst; Mäzenatentum; Architektur; Il Gesù -- Rom; Rom; Chiesa del Gesù (Rome, Italy) / Exhibitions; Chiesa del Gesù (Rome, Italy); Christian art and symbolism / Italy / Rome / Modern period, 1500- / Exhibitions; Jesuit art / Exhibitions; Art, Baroque / Italy / Rome / Exhibitions; Art, Italian / Italy / Rome / Exhibitions; Art, Baroque; Art, Italian; Christian art and symbolism / Modern period; Jesuit art; Italy / Rome; Since 1500; Exhibition catalogs; Ausstellungskatalog -- Fairfield University Art Museum -- 02.02.2018-19.05.2018 -- Fairfield, Conn.